Evaluation of Fabrication Process for Molybdenum Disulfide Quantum Dots in Organic Solvents Using Ultrasonic and Thermal Exfoliation - Hon-Pan Yiu; Cheng-Jun Wu; Chuan Li; Cho-Yin Lee (Engineering Proceedings)
When the size of the molybdenum disulfide (MoS2) is reduced to a few nanometers, a distinctive photoluminescence is observed due to the strong effect of quantum confinement. In this study, we fabricated MoS2 quantum dots (QDs) using a simple and green process. We dissolved the powder of MoS2 in various solvents, including N-Methyl-2-pyrrolidone (NMP), ethanol (EtOH), and deionized water (DIW), and dispersed it by sonication or solvent-thermal exfoliation. The synthesized MoS2 QDs were characterized for their optical properties. Transmission electron microscopy (TEM) was used to analyze the particle size and morphology; UV-visible spectrometer and photoluminescence tests were employed to measure optical absorption, bandgaps, and optical emission. The photothermal test was designed for the evaluation of the optothermal conversion. In vitro cultures of 3T3 fibroblast cells were evaluated for the biocompatibility of the MoS2 QDs. Results from different experiments were cross-examined and analyzed to understand the relation among different syntheses, microstructures, and optical properties of MoS2 QDs. A yield of 15% MoS2 QDs was obtained when synthesized in ethanol by thermal exfoliation. They also showed satisfactory optothermal effects.